Oxytocin receptor gene polymorphisms (rs53576) and early paternal care sensitize males to distressing female vocalizations - Truzzi, Anna (2018)
The oxytocinergic system is highly involved in social bonding and early caregiver–infant interactions. Here, we hypothesize that oxytocin receptor (OXTR) gene genotype and parental bonding history interact in influencing social development. To address this question, we assessed adult males’ arousal (heart rate changes) in response to different distress vocalizations (human female, human infant and bonobo). Region rs53576 of the OXTR gene was genotyped from buccal mucosa cell samples, and a self-report Parental Bonding Instrument was used (which provide information about parental care or parental overprotection). A significant gene–environment interaction between OXTR genotype and parenting style was found to influence participants’ social responsivity to female cry vocalizations. Specifically, a history of appropriate paternal care in participants accentuated the heightened social sensitivity determined by G/G homozygosity, while higher versus lower paternal overprotection lead to distinct levels of physiological arousal particularly in A carriers individuals. These results add to our understanding of the dynamic interplay between genetic susceptibility and early environmental experience in shaping the development of appropriate social sensitivity in males.